Bioactivity, crystal and molecular structure of vanadyl(III) complex with N-salicyloyl − N’(3,5-ditertbutyl-2-hydroxy)benzylidene hydrazine - YALÇIN, BAHATTİN (My University, 2024)
N-salicyloyl-N’-(3,5-ditertbutyl-2-hydroxy)benzylidene hydrazine (H3sahz) and its complex with VO(III) have been synthesized. The molecular and crystal structure of the [(VO)2(sahz)2(C2H5O)2(C2H5OH)] complex by X-ray diffraction, as well as IR and electronic spectra, EPR spectrum etc., have been studied. The structure of the investigated VO(III) complex consists of binuclear units in which the monomeric complex molecules are linked to each other through vanadyl oxygen atom. Monomeric complexes differ between themselves in the character of coordination. Both vanadium atoms have a distorted octahedral environment. The biological activity of this compound has been studied. Lastly, the activities of the studied ligand against various enzyme proteins including acetylcholinesterase (AChE), butrylcholinesterase (BChE) and α-glycosidase (α-Gly) enzyme were compared. ChE inhibitory activities of the new complex against α-Gly, AChE and BChE were determined by Tao and Ellman\"s methods. The new complex was shown to have IC50 values of 42.60 µM for BChE, 91.43 µM for AChE, and 196.49 µM for α-glycosidase.
Keywords: Kimya; Fizikokimya; İnorganik Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Inorganic Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; KİMYA, İNORGANİK VE NÜKLEER; KİMYA, FİZİKSEL; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; CHEMISTRY, INORGANIC & NUCLEAR; CHEMISTRY, PHYSICAL; MATERIALS SCIENCE, MULTIDISCIPLINARY; Fiziksel ve Teorik Kimya; Fizik Bilimleri; İnorganik kimya; Malzeme Kimyası; Physical and Theoretical Chemistry; Physical Sciences; Materials Chemistry; Complexes VO(III); Hydrazones; Molecular docking; Salicylic acid hydrazide; Thermal analysis; X-ray diffraction